Accessing and engaging with primary health care services following discharge from forensic secure services: the perspectives of service users and mental health practitioners. Issue 2 (3rd July 2021) - Samuels, Emily; Moran, Nicola
Abstract : Purpose: Physical health inequalities and mortality rates are higher amongst individuals with severe mental illness (SMI), including among forensic populations, than the general population. This paper aims to explore the experiences of individuals accessing primary health care following discharge from secure services, and the practitioners who support them. Design/methodology/approach: Face-to-face qualitative interviews were conducted with service users (n = 4) and mental health practitioners ( n = 4) within a forensic community mental health team in one NHS Trust in England in 2019. Data were analysed using the Interpretative Phenomenological Analysis. Findings: Four super-ordinate themes emerged: perceived importance of physical health, agency, responsibility and relationships. Service users mostly saw themselves as passive recipients of health care and prioritised their mental health over their physical health. Close working relationships meant that mental health practitioners were often the first contact for service users with any health issue and thus felt a sense of responsibility for their physical health care. Service users who did access primary care reported that consistency of professional, feeling understood and listened to without judgement or stigma were important. Practical implications: Interventions for service users that include practicalities and strategies to facilitate independence in physical health care, and collaborative working between primary care and forensic mental health services, are encouraged. Originality/value: This study highlights some of the unique challenges in forensics around improving physical health outcomes for individuals with SMI.